2020
DOI: 10.1101/2020.07.31.230706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinguishing between recent balancing selection and incomplete sweep using deep neural networks

Abstract: 1AbstractBalancing selection is an important adaptive mechanism underpinning a wide range of phenotypes. Despite its relevance, the detection of recent balancing selection from genomic data is challenging as its signatures are qualitatively similar to those left by ongoing positive selection. In this study we developed and implemented two deep neural networks and tested their performance to predict loci under recent selection, either due to balancing selection or incomplete sweep, from population genomic data.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 90 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…In summary, we have shown that CNNs are a powerful approach to detecting adaptive introgression and can recover both known and novel selection candidates that were introduced via admixture. As in previous applications to other problems in the field (Sheehan & Song, 2016; Flagel et al ., 2018; Schrider & Kern, 2018; Villanea & Schraiber, 2019; Mondal et al ., 2019; Torada et al ., 2019; Isildak et al ., 2020), this exemplifies how deep learning can serve as a very powerful tool for population genetic inference. This type of technique may thus be a useful resource for future studies aiming to unravel our past history and that of other species, as statistical methodologies and computational resources continue to improve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, we have shown that CNNs are a powerful approach to detecting adaptive introgression and can recover both known and novel selection candidates that were introduced via admixture. As in previous applications to other problems in the field (Sheehan & Song, 2016; Flagel et al ., 2018; Schrider & Kern, 2018; Villanea & Schraiber, 2019; Mondal et al ., 2019; Torada et al ., 2019; Isildak et al ., 2020), this exemplifies how deep learning can serve as a very powerful tool for population genetic inference. This type of technique may thus be a useful resource for future studies aiming to unravel our past history and that of other species, as statistical methodologies and computational resources continue to improve.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the need to compress data into summary statistics (which might miss important features) or solve complex analytical theory, deep learning techniques are increasingly becoming a popular solution to address problems in population genetics. These problems include the inference of demographic histories (Sheehan & Song, 2016;Flagel et al, 2018;Villanea & Schraiber, 2019;Mondal et al, 2019;Sanchez et al, 2020), admixture (Blischak et al, 2020), recombination (Chan et al, 2018;Flagel et al, 2018;Adrion et al, 2020b) and natural selection (Schrider & Kern, 2018;Sheehan & Song, 2016;Torada et al, 2019;Isildak et al, 2020). Deep learning is a branch of machine learning that relies on algorithms structured as multi-layered networks, which are trained using known relationships between the input data and the desired output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods can be utilized with large genomic datasets and multiple populations, allowing for hypothesis testing between populations with different attributes. Moreover, the varied modeling techniques employed by these methods permits them to directly account for the expected correlation structure among summary statistics across genomes (such as with Trendsetter [ 59 ] and SURFDAWave [ 60 ]), as well as to even automatically estimate genomic features from raw genotype calls that yield the highest prediction accuracies (such as with the methods of Flagel et al [ 56 ], ImaGene [ 61 ], and BaSe [ 62 ]). One particular caveat of these methods is that an accurate demographic model is generally needed for the production of training data.…”
Section: Methods For Detecting Positive Selectionmentioning
confidence: 99%
“…The deluge of polymorphism data available from contemporary sequencing technologies has fueled interest in both method development (e.g. Bitarello et al , 2018 ; Cheng and DeGiorgio, 2019 , 2020 ; DeGiorgio et al , 2014 ; Isildak et al , 2021 ; Sheehan and Song, 2016 ; Siewert and Voight, 2017 , 2020 ) and empirical data analysis (e.g. Croze et al , 2017 ; Leffler et al , 2013 ; Teixeira et al , 2015 ) on balancing selection.…”
Section: Introductionmentioning
confidence: 99%